2017
DOI: 10.1371/journal.pone.0181018
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis, cytotoxicity and antitumour mechanism investigations of polyoxometalate doped silica nanospheres on breast cancer MCF-7 cells

Abstract: Polyoxometalates (POMs) have shown the potential anti-bacterial, anti-viral and anti-tumor activities. In order to improve their physiological stability and antitumour activity for medical application, K2Na[AsIIIMo6O21(O2CCH2NH3)3]·6H2O doped silica nanospheres (POM@SiO2) with diameters of ~40 nm have been synthesized by the water-in-oil microemulsion method in this study. The obtained spheres were morphologically uniform nanosized and nearly monodispersed in solution. The nanoparticles had high entrapment eff… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
21
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 39 publications
(21 citation statements)
references
References 51 publications
0
21
0
Order By: Relevance
“…Figure 6 c shows an increase in the nuclear fluorescence intensity after 72 h of cells treated with ANS-PLNPs and PEG-ANS-PLNPs as compared with the intensity at time 0. This points towards the presence of a significant population of DNA-damage related cell death due to the release of the ANS from the PLNP [ 48 , 49 ].…”
Section: Discussionmentioning
confidence: 99%
“…Figure 6 c shows an increase in the nuclear fluorescence intensity after 72 h of cells treated with ANS-PLNPs and PEG-ANS-PLNPs as compared with the intensity at time 0. This points towards the presence of a significant population of DNA-damage related cell death due to the release of the ANS from the PLNP [ 48 , 49 ].…”
Section: Discussionmentioning
confidence: 99%
“…The formation of Ag nanoparticles was observed [27] by Ultraviolet-visible (UV-Vis) spectrophotometer (Thermo Scientific Multiscan Spectrum 1500, USA) with a range of 200–800 nm. The functional groups on AgNPs were validated with Fourier-transform infrared (FTIR) spectroscopy using in the range of 400–4000 cm -1 (Shimadzu IR 8000, Japan).…”
Section: Methodsmentioning
confidence: 99%
“…Propidium iodide (PI) and Hoechst 33342 double staining [27, 29] in cultured MCF7 cells were measured to detect apoptosis after the treatment of AgNPs with PDT. Cells (1 × 10 5 ) were cultured in a six-well plate and treated with different concentrations of AgNPs then eight hours incubated with PDT exposed cells.…”
Section: Methodsmentioning
confidence: 99%
“…W 6+ , V 5+ ). Earlier studies showed that these inorganic drug candidates possess potential anti-viral, [10][11][12] -bacterial, 13,14 -protozoal, 15 -tumor, 16,17 -Alzheimer 18 and -diabetic activities. 8,9 However, their molecular modes of action are poorly understood.…”
Section: Introductionmentioning
confidence: 99%